Management of Irrigation System under Scarcity conditions - Thiruvenkataswamy, KR. (Journal of Soil and Water Conservation, 2022)
Irrigation projects are executed to ensure assured irrigation water to raise crops as a measure of insurance against crop failures. Most often, the vagaries of monsoon rains come in the way of normal supply of irrigation water to the command area. Owing to inadequate rainfall in the catchments, the Periyar-Vaigai reservoirs in Tamil Nadu did not get filed up to the normal capacity and in time during the year 1982. This situation had compelled late release of water and lesser quantum of water for irrigation of the command area. The impact of innovations such as improvement in conveyance and field application efficiencies, rotation of irrigation among the cultivators within the ten hectare blocks in the context of insufficient discharge where studied The deficiency of rainfall, the rate of discharge and the yield of rice crop were analysed and it has been found that the water use efficiency per millimeter of irrigation water had increased to a significant extent as a result of the imporved practices. The strategies employed in Periyar- Vaigai irrigation project to meet the inadequate and untimely supply of irrigation water and their impact on productivity are discussed in this paper.